Wykorzystanie opcji realnych w wycenie projektów inwestycyjnych na przykładzie przemysłu farmaceutycznego - Antkiewicz, Sławomir (The Real Options Method for Evaluating Investment Projects on the Example of Pharmaceutical Industry, 2007)
The following work presents the modern management of enterprise's finance, namely a real options method. It is based on analogy to finance options. Their evaluation is based on Black-Scholes formula. The real options method is used in many sections of economy. Pharmaceutical corporations use the options method most often. In pharmaceutical industry, real options are used often in the new drug development process as for instance the research on the antibiotic Tribactam of GlaxoSmithKlein. During the progress of this project, GSK did an evaluation of abandon option and continued the project by producing oral or in vein version of the drug.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 13-22